Age-related loss of stress-induced nuclear proteasome activation is due to low PARP-1 activity - YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE INC, 2011)
Changes in protein turnover are among the dominant metabolic changes during aging. Of special importance is the maintenance of nuclear protein homeostasis to ensure a coordinated cellular metabolism. Therefore, in the nucleus a special PARP-1-mediated mechanism of proteasomal activation exists to ensure a rapid degradation of oxidized nuclear proteins. It was already demonstrated earlier that the cytosolic proteasomal system declines dramatically with aging, whereas the nuclear proteasome remains less affected. We demonstrate here that the stress-mediated proteasomal activation in the nucleus declines during replicative senescence of human fibroblasts. Furthermore, we clearly show that this decline in the PARP-1-mediated proteasomal activation is due to a decline in the expression and activity of PARP-1 in senescent fibroblasts. In a final study we show that this process also happens in vivo, because the protein expression level of PARP-1 is significantly lower in the skin of aged donors compared to that of young ones. Therefore, we conclude that the rate-limiting factor in poly(ADP-ribose)-mediated proteasomal activation in oxidative stress is PARP-1 and not the nuclear proteasome itself. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Protein oxidation; Aging; Proteasome; PARP; Nucleus; Free radicals; BRAIN PROTEIN OXIDATION; HUMAN MRC-5 FIBROBLASTS; ADP-RIBOSE-POLYMERASE; HUMAN BJ FIBROBLASTS; POLY(ADP-RIBOSE) POLYMERASE; OXIDIZED PROTEINS; CELLULAR SENESCENCE; ALZHEIMER-DISEASE; PROLIFERATIVE SENESCENCE; MULTICATALYTIC PROTEASE